Synthesis of a novel Cu/DPA-MOF/OP/CS hydrogel with high capability in antimicrobial studies - Jasim Al-Khafaji, Hanadi Hadi; Alsalamy, Ali; Abed Jawad, Mohammed; Ali Nasser, Hind; Dawood, Ashour H.; Hasan, Saif Yaseen; Ahmad, Irfan; Gatea, M. Abdulfadhil; Younis Albahadly, Waleed Khaled (Frontiers in Chemistry, 2023)
Today, with the indiscriminate use of antibiotics, we face the resistance of some bacterial strains against some antibiotics. Therefore, it is essential to report and synthesize new compounds with antimicrobial properties. A novel copper/dipicolinic acid–metal–organic framework cross-linked oxidized pectin and chitosan (Cu/DPA-MOF/OP/CS) hydrogel polymer was synthesized under environmental conditions with the controllable process, which uses biodegradable polymer compounds such as pectin and chitosan in its structure. The efficient physicochemical features of the synthesized Cu/DPA-MOF/OP/CS hydrogel using SEM, FT-IR, TGA, BET, XRD, and EDS/mapping were identified and confirmed. The newly synthesized Cu/DPA-MOF/OP/CS hydrogel showed activity against Gram-positive and Gram-negative bacterial strains and fungal species, and significant antibacterial and antifungal properties were observed. In antibacterial activity, the MIC against Gram-positive species was in the range of 16–128 mg/mL, the MIC against Gram-negative species was in the range of 64–256 mg/mL, and the MIC against fungal species was in the range of 128–512 mg/mL. In antimicrobial evaluations, in addition to the MIC test, the MBC test, the MFC test, and the IZD test were performed, and the results were reported. The results were compared with commercial antibiotics in the market. Development of novel nanostructures based on hydrogel polymers with distinctive functionality can affect the performance of these nanostructures in different areas.